Determinan gejala kecemasan pasien gagal ginjal kronik pada fase awal menjalani hemodialisa - Kharisma, Asdilia; Muzaenah, Tina (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Chronic kidney disease (CKD) is a condition of decreased kidney function that lasts for more than three months. Patients undergoing hemodialysis to treat CKD often experience decreased quality of life and various physical and psychological symptoms, one of which is anxiety. Anxiety and depression are often experienced, especially by patients who have just started hemodialysis therapy. Purpose: To determine the most dominant determinants of anxiety symptoms in chronic kidney disease patients undergoing early hemodialysis. Method: This descriptive analytical study was conducted at the Hemodialysis Unit of Prof. Margono Soekarjo Regional Hospital, Purwokerto, in December 2024. The population was all patients aged 20-60 years who had been undergoing hemodialysis for less than one year, with a sample size of 71 respondents. Results: The dominant symptoms of anxiety from physical and psychological aspects of anxiety symptoms are sleep disturbances (12.9%), nervous (autonomic) symptoms (10.6%) namely dry mouth and dizziness, anxious feelings (10.6%) namely feelings of anxiety and discomfort, tension (10.3%) namely the state of being unable to rest and sleep peacefully, somatic symptoms (8.4%) namely pain and aches in the muscles, and digestive symptoms (8%) namely nausea and vomiting. Conclusion: The most dominant determinants of anxiety symptoms in chronic kidney failure patients undergoing hemodialysis are behavioral responses in the form of sleep disturbances, neuromuscular system symptoms (autonomic symptoms), affective responses in the form of anxiety and tension, neuromuscular system symptoms (somatic symptoms), and gastrointestinal system symptoms (digestive symptoms). Suggestion: Future research can use anxiety questionnaires that focus on psychological aspects. Furthermore, this study only used questionnaires for data collection, so interviews can be used to gather symptoms experienced by chronic kidney failure patients. Keywords: Anxiety; Chronic Kidney Failure; Hemodialysis. Pendahuluan: Gagal ginjal kronik (GGK) merupakan kondisi penurunan fungsi ginjal yang berlangsung lebih dari tiga bulan. Pasien yang menjalani hemodialisis untuk menangani GGK sering mengalami penurunan kualitas hidup dan berbagai gejala fisik dan psikologis, salah satunya kecemasan. Kecemasan dan depresi sering dialami, terutama oleh pasien yang baru memulai terapi hemodialisis. Tujuan: Untuk mengetahui determinan gejala yang paling dominan dari gejala kecemasan pada pasien gagal ginjal kronik fase awal menjalani hemodialisa. Metode: Penelitian deskriptif analitik, dilaksanakan di Ruang Hemodialisa Rumah Sakit Umum Daerah Prof. Dr. Margono Soekarjo Purwokerto pada bulan Desember 2024. Populasi dalam penelitian ini adalah semua pasien dengan usia 20-60 tahun yang sedang menjalani hemodialisa kurang dari satu tahun dengan jumlah sampel yang digunakan sebanyak 71 responden. Hasil: Gejala kecemasan yang dominan dari gejala-gejala kecemasan pada aspek fisik dan psikologis adalah gangguan tidur (12,9%), gejala saraf (autonom) (10,6%) yaitu keadaan mulut kering dan kepala pusing, perasaan cemas (10,6%) yaitu keadaan cemas dan firasat buruk, ketegangan (10,3%) yaitu keadaan tidak dapat istirahat dan tidur dengan tenang, gejala somatik (8,4%) yaitu sakit dan nyeri di otot-otot, dan gejala pencernaan (8%) yaitu keadaan mual dan muntah. Simpulan: Determinan gejala yang paling dominan dari gejala-gejala kecemasan pada pasien gagal ginjal kronik fase awal menjalani hemodialisa adalah pada respon perilaku berupa gangguan tidur, sistem neuromuscular berupa gejala saraf (autonom), respon afektif berupa perasaan cemas dan ketegangan, sistem neuromuscular berupa gejala somatik, dan sistem gastrointestinal berupa gejala pencernaan. Saran: Penelitian selanjutnya dapat menggunakan kuesioner kecemasan yang fokus pada aspek psikologis. Selain itu, pengambilan data dalam penelitian ini hanya menggunakan kuesioner, sehingga dapat menggunakan wawancara dalam mengumpulkan gejala-gejala yang dialami oleh pasien gagal ginjal kronik. Kata Kunci: Gagal Ginjal Kronik (GGK); Hemodialisis; Kecemasan.